Potentially toxic metals in the high-biomass non-hyperaccumulating plant amaranthus viridis: human health risks and phytoremediation potentials - Yap, Chee Kong; Yaacob, Aziran; Tan, Wen Siang; Al-Mutairi, Khalid Awadh; Cheng, Wan Hee; Wong, Koe Wei; Berandah Edward, Franklin; Ismail, Mohamad Saupi; You, Chen-Feng; Chew, Weiyun; Nulit, Rosimah; Ibrahim, Mohd Hafiz; et al. (MDPI, 2022)
Human health risk and phytoremediation of potentially toxic metals (PTMs) in the edible vegetables have been widely discussed recently. This study aimed to determine the concentrations of four PTMs, namely Cd, Fe, Ni, and Zn) in Amaranthus viridis (leaves, stems, and roots) collected from 11 sampling sites in Peninsular Malaysia and to assess their human health risk (HHR). In general, the metal levels followed the order: roots > stems > leaves. The metal concentrations (µg/g) in the leaves of A. viridis ranged from 0.45 to 2.18 dry weight (dw) (0.05–0.26 wet weight (ww)), 74.8 to 535 dw (8.97–64.2 ww), 2.02 to 7.45 dw (0.24–0.89 ww), and 65.2 to 521 dw (7.83–62.6 ww), for Cd, Fe, Ni, and Zn, respectively. The positive relationships between the metals, the plant parts, and the geochemical factions of their habitat topsoils indicated the potential of A. viridis as a good biomonitor of Cd, Fe, and Ni pollution. With most of the values of the bioconcentration factor (BCF) > 1.0 and the transfer factor (TF) > 1.0, A. viridis was a very promising phytoextraction agent of Ni and Zn. Additionally, with most of the values of BCF > 1.0 and TF < 1.0, A. viridis was a very promising phytostabiliser of Cd and Fe. With respect to HHR, the target hazard quotients (THQ) for Cd, Fe, Pb, and Zn in the leaves of A. viridis were all below 1.00, indicating there were no non-carcinogenic risks of the four metals to consumers, including children and adults. Nevertheless, routine monitoring of PTMs in Amaranthus farms is much needed.